Thomson Learning's certified business manager (Thomson/South-Western, 2004)
The CBM is the only generalists' certification designed for all business specialists and is the most integrated exam available in the business management field. The CBM is to a business manager as the CPA is to an accountant as the CFA is to an investment analyst. Finally, there is one source to help you streamline CBM exam preparation efforts to achieve success! The CBM Exam (www.cbmexam.com) consists of three parts-- Part 1: Core Areas, Part 2: Functional Areas, Part 3: Integrated Areas. Preparation for each part of the exam is covered in two volumes providing you with a thorough review of both theory and practice for success on the exam. Volume 1 provides review of the theory essential for successful business application in core areas. Volume 2 (ISBN: 0-324-27328-2) delivers highly-focused self-assessment practice for Part 1 of the CBM Exam